Pemberian Murotal Surah Maryam terhadap Kejadian Postpartum Blues pada Ibu Postpartum - Salma, Salsabil; Rahayuningsih, Faizah Betty (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the effect of reciting Surah Maryam on postpartum blues and anxiety levels in postpartum mothers. The research method used a quasi-experimental design with a pretest-posttest design with a control group. The results showed a significant decrease in anxiety scores and postpartum blues scores among mothers after the intervention (p <0.001). In conclusion, Surah Maryam recitation significantly reduced anxiety and postpartum blues, which could be an alternative non-pharmacological approach to support the mental health of mothers after childbirth. Keywords: Postpartum Mothers, Anxiety, Murotal Surah Maryam, Postpartum Blues